Synthesis of Trifluoromethyl-Substituted Cyclopentanes through Boron-Radical-Catalyzed Cycloaddition Reaction of Trifluoromethyl-Substituted Alkenes - Qin, Lulu; Yu, Tao; Ding, Zhengwei; Zhao, Min; Li, Pengfei (Synthesis, 2025)
A highly efficient protocol for the synthesis of trifluoromethyl-substituted cyclopentanes, a structural motif ubiquitous in bioactive compounds and natural products, via boron-radical-catalyzed (3+2) cycloaddition of aroylcyclopropanes and trifluoromethyl-substituted alkenes was developed. Employing readily available precursors, this modular, atom-economical, metal-free, and operationally simple process was compatible with diverse functional groups, giving the products in generally good to high yields. Trifluoromethyl-substituted bicyclo[2.1.1]hexanes (BCHs) were analogously prepared.
Keywords: cycloaddition; trifluoromethyl-substituted alkenes; boron radicals; catalysis; cyclopentanes